Engel Series and Cohen-Egyptian Fraction Expansions - Vichian Laohakosol (International Journal of Mathematics and Mathematical Sciences, 2009)
Two kinds of series representations, referred to as the Engel series and the Cohen-Egyptian fraction expansions, of elements in two different fields, namely, the real number and the discrete-valued non-archimedean fields are constructed. Both representations are shown to be identical in all cases except the case of real rational numbers.